A systematic study of the effect of the hard end-group composition on the microphase separation, thermal and mechanical properties of supramolecular polyurethanes. (19th December 2016) - Merino, Daniel Hermida; Feula, Antonio; Melia, Kelly; Slark, Andrew T.; Giannakopoulos, Ioannis; Siviour, Clive R.; Buckley, C. Paul; Greenland, Barnaby W.; Liu, Dan; Gan, Yu; Harris, Peter J.; Chippindale, Ann M.; et al.
Abstract: This paper reports a systematic study on a series of supramolecular polyurethanes that possess microphase separated morphologies which afford elastic materials at room temperature. Combinations of urea and/or urethane linkers in addition to a phenyl spacer have been used to study the effect of the rigidity of the hard end group segments as well as the hydrogen bonding capability of the urethane-urea linker units. Small angle X-ray scattering (SAXS) experiments have revealed characteristic microphase separated morphologies. Wide angle X-ray scattering (WAXS) was used to probe the lateral packing of the urethane and/or urea within the hard segments. Differential scanning calorimetry (DSC) analysis confirmed that unsymmetrical soft/hard segment phases have been achieved by varying the urethane/urea content. Transmission electron microscopy (TEM) and atomic force microscopy (AFM) determined that a 1-D fibrillar structure was obtained when the hard segment featured ureas whereas a 3-D structure was achieved when a combination of urea and urethane groups was used, giving rise to enhanced elongation properties. Finally, we present mechanical testing data in which oscillatory rheology at a range of frequencies and temperatures has revealed the effect of the connectivity of the hard segments on the relaxation times of the supramolecular chains. Tensile tests showed that end groups with ureas or a combination of a urea and urethane yielded elastic materials with strengths of ca. 5 MPa at room temperature. Graphical abstract: Highlights: End-group composition affects microphase separation of supramolecular polyurethanes. End-group composition affects thermal properties of supramolecular polyurethanes. End-group composition affects mechanical properties of supramolecular polyurethanes.